Assessing and improving the automatic ordering of perishable products: A case study in a major retailer - Ferreira, L.; Silva, J.; Rocha, D. (Proceedings of 20th EurOMA - Operations Management at the Heart of Recovery, 2013)
The reported exploratory study aimed at evaluating an automated ordering system for fruit and vegetables within a large retailer. An innovative pilot-test was run in one representative store. During three months, the store manager committed himself to the ‘‘best’ working practices and to accept the central computer schedule as mandatory, resulting into: sharp reduction in schedule changes; sales and average coverage ratio keeping Past behaviour patterns and, the waste indicator showing a systematic decrease. These results revealed the need for different forecasting strategies for distinct demand patterns, in order to improve performance, as a practitioner contribution.